Analyses of market alliance stability of hydropower stations. Issue 1 (11th June 2019) - Liu, Yue; Ma, Guangwen; Huang, Weibin; Chen, Shijun; Zhang, Shuai
Abstract : A new round of reform of China's electricity market was launched in 2015 to encourage competition among power generation companies. For cascade hydropower stations under multi-partite ownership, an alliance has become a way to improve competitiveness, but the stability of such alliances is affected by multiple factors. Because of the fierce competition caused by incomplete marketisation and oversupply, some hydropower stations show bounded rationality. In this work, the replicator dynamic mechanism was used to analyse the alliance stability of cascade hydropower stations: this provided a two-dimensional (2D) continuous dynamic system and the specific steps for its solution. After detailed analysis of the existence and stability of the equilibrium solution in the 2D continuous dynamic system and the Jacobian matrix, the parameters for convergence process analysis were assessed. The numerical simulation showed that the alliance is positively related to the common additional income and the penalty factor, and has a negative correlation with a single party's initial investment. It was also found that there is an optimal proportion of common additional income distribution, which makes the alliance most likely to succeed.